Reviving the forgotten: breathing life into urban wastelands through skateboarding and decolonial placemaking in Nairobi, Kenya - Tsipis, Athanasios; Mashreghi, Sepandarmaz (Frontiers in Sports and Active Living, 2025)
Skateboarding in Nairobi, Kenya, offers young people ways of asserting subjectivity, reimagining the city through movement, care, and shared presence. Based on semi-structured interviews, field observations, and sensory ethnography, this study traces how skateboarders transform overlooked sites—plazas, rooftops, and improvised parks—into spaces of community building, ecological care, and affective belonging. Grounded in decolonial thought, Indigenous teachings, and feminist ethics of care, the analysis frames skateboarding as a collective practice through which personhood is shaped, care for community and environment is sustained, and otherwise ways of being in the city are made possible. The findings show how Nairobi's skateboarders negotiate colonial and patriarchal histories and structures, generate affective ecologies of belonging through sound and movement, and practice feminist placemaking through accountability and solidarity. Clean-ups, DIY ramp-building, and the reclaiming of wastelands illustrate how skaters convert abandonment into commons and environmental responsibility. Such practices are not without tension, as skateboarders navigate precarity, layered marginalization, policing, stigmatization, the absence of formal facilities, complicity and conflicts within their own collectives. Ultimately this paper demonstrates that Nairobi's skateboarding practices are not only leisure, but also affective and relational world-making that point toward alternative decolonial urban futures.